Short‐term outcomes following development of a dedicated pelvic exenteration service in a tertiary centre. Issue 10 (22nd July 2022) - Traeger, Luke; Bedrikovetski, Sergei; Oehler, Martin K.; Cho, Jonathan; Wagstaff, Marcus; Harbison, Jack; Lewis, Mark; Vather, Ryash; Sammour, Tarik
Abstract: Background: Pelvic exenteration surgery (PE) offers potentially curative resection for locally advanced malignancy but is associated with significant complexity and morbidity. Specialised teams are recommended to achieve optimal patient outcomes. This study aims to analyse short‐term outcomes at a tertiary setting before and after creating a dedicated PE service. Methods: Patients undergoing PE between 2008 and October 2021 at the Royal Adelaide Hospital and St. Andrews Hospital in South Australia were included, with prospective data collection since June 2017. Patients operated on prior and post the creation of the PE service were compared via univariate analyses. Results: In total, 113 patients were included, with a significant increase in volume of cases post creation of the PE service, ( n = 46 pre versus n = 67 post). There were significant differences in the type of neoadjuvant therapy and patient co‐morbidity, with more advanced disease stage and a higher likelihood of bone involvement ( P < 0.05) in the latter period. An increased proportion of patients had flap reconstruction (40.3 versus 33.9%, P = 0.010) as well as lateral lymph node dissection (13.4 versus 2.2%, P = 0.046). Despite this, peri‐operative outcomes such as urosepsis (11.9 versus 28.3%, P = 0.028) and Clavien‐Dindo grade of complications grade improved. R0 resections were achieved in 93.9% of curative cases (93.9 versus 84.2%, P = 0.171). Conclusion: The development of a PE service significantly improved short term patient outcomes, despite the inclusion of patients with more advanced disease and comorbidity. Abstract : The development of a dedicated PE service at the Royal Adelaide Hospital and St Andrews Hospital in 2017, significantly improved short term patient outcomes, despite the inclusion of patients with more advanced disease and comorbidity. This supports a dedicated specialised multidisciplinary approach to locally advanced pelvic malignancy.